Graduación en el Teatro Popular Melico Salazar, abril, 2011. (UNED, 2011)
dos personas posando con sus títulos. Al fondo Orlando Morales, Luis Guillermo Carpio, Nidia Lobo, Humberto Aguilar y Nancy Vasquez